2017
DOI: 10.4067/s0718-58392017000400382
|View full text |Cite
|
Sign up to set email alerts
|

Maize stover biochar increases urea ( 15 N isotope) retention in soils but does not promote its acquisition by plants during a 4-year pot experiment

Abstract: 382Biochar as a soil amendment has been shown to improve soil quality and crop growth. However, biochar's effect on urea-N use efficiency in long term is not well elucidated. Here we studied urea-N ( 15 N isotope) allocation in plants and soil in the presence of maize (Zea mays L.) stover biochar (equivalent to 46 t ha -1 ) during a 4-yr pot trial. Results showed that biochar only increased maize biomass (about 9%) with high amount of urea addition, which indicates the increased maize dry weight by biochar app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…A similar positive impact of biochar on N recovery result of also observed from a previous study [76]. Liu et al [77] demonstrated that the inclusion of biochar with urea accelerated fertilizer N retention and increased N mineralization in the soil, which possibly resulted in enhanced N uptake with the improved FNR of rice.…”
Section: Nitrogen Use Efficiency (Nue) and Recoverysupporting
confidence: 81%
“…A similar positive impact of biochar on N recovery result of also observed from a previous study [76]. Liu et al [77] demonstrated that the inclusion of biochar with urea accelerated fertilizer N retention and increased N mineralization in the soil, which possibly resulted in enhanced N uptake with the improved FNR of rice.…”
Section: Nitrogen Use Efficiency (Nue) and Recoverysupporting
confidence: 81%
“…For zucchini (corgette) crops, biochar increased N and P use efficiency has been noted on calcareous sandy soil (El-Eyuoon et al, 2017). In maize, it effectively improved the N use efficiency and yield on poor sandy soil (Omara et al, 2020) and reduced N loss from loamy soil (Liu, Cheng et al, 2017;Liu, He et al, 2017).…”
Section: Nutrient Use Efficiencymentioning
confidence: 99%
“…Meena et al (2020) have reported enhanced soil organic carbon, ammonium-N, and nitrate-N concentration in soil with the mixed application of biochar and N fertilizer than without biochar. However, a 4-year pot experiment by (Liu, Cheng et al, 2017;Liu, He et al, 2017) claimed an increase in retention of urea in soil but without acquisition by the plant when maize stover biochar was added. Furthermore, Melaku et al (2020) observed a lower marginal agronomic efficiency with biochar amendment than sole N predicting that plants utilized applied nutrients more efficiently without biochar at low doses of chemical fertilizers.…”
Section: Nutrient Use Efficiencymentioning
confidence: 99%